Intellectual Capital, Innovative Performance and the Moderating Effect of Entrepreneurial Orientation among SMEs in Jordan - Alzuod, Mohammad Abdalkarim; Isa, Mohd Faizal Mohd; Othman, Siti Zubaidah bt. (International Review of Management and Marketing, 2017)
The aim of this study investigates empirically the role of moderating effect of entrepreneurial orientation in relationship between intellectual capital and innovative performance among Jordanian SMEs. Data was gathered by using a questionnaire survey. The questionnaire was distributed to a sample of 600 managers / owners from Jordanian SMEs. 325 usable questionnaires were returned. PLS SEM technique had been applied to analyses the data. The findings showed that dimensions of intellectual capital (human capital and customer capital) were found positively and significantly related to innovative performance. In addition, this study supports the effect of entrepreneurial orientation that moderate partially in relationship between intellectual capital and innovative performance. Keywords: Innovative Performance; Intellectual Capital; Entrepreneurial Orientation; SMEs; Jordan JEL Classifications: L26, O34